Professional development among academic staff at selected Malaysian public universities: preliminary findings of the impact of the Basic Teaching Methodology Course (BTMC) - Othman, Azam; Dahari, Zainurin (Center for Promoting Ideas (CPI), 2011)
Despite the growing number of research findings that indicate the importance of professional development in academic teaching and learning, the visible impact of staff participation in professional development on effective teaching practices in Higher Education is not significant. As such, the Ministry of Higher Education of Malaysia has strongly urged the universities to sonduct the Basic Teaching Methodology Course (BTMC) for new academic staff. A self-administered questionnaire survey was carried out in four selected universities offering the BTMC. It was found that participants of the BTMC had positive perceptions about the course. They were happy for the oppurtunities offered by their respective universities to improve their knowledge and skills. They believed that the BTMC is useful in developing their academic potential. However, the study also found that the impact of the BTMC on actual teaching practices is minimal. This paper is a report of the findings of the study, and discusses the benefits and the extent to which the academic staff utilized the knowledge and skills learned from the BTMC.